The growth of the liberal soul - Walsh, David (Univ. of Missouri Press, 1997)
Unique in combining contemporary political relevance with historical depth, The Growth of the Liberal Soul brings together two approaches that are often treated separately. Walsh elaborates on the existential core of the liberal political tradition by way of an investigation of the historical sources and the raging contemporary debates